Systematic study of the genus Senometopia Macquart (Diptera: Tachinidae) from the eastern Palaearctic and Oriental regions. (2nd January 2023) - Shima, Hiroshi; Tachi, Takuji
ABSTRACT: Eighty-eight species of Senometopia Macquart, 1834 (Diptera, Tachinidae) from the eastern Palaearctic and Oriental regions are revised. Argyrothelaira Townsend, 1916 and Catacarcelia Townsend, 1927 are newly synonymized with Senometopia. Forty-two new species are described. The following 11 new combinations are proposed: S. aurata (Townsend, 1927) comb. nov., S. bakeri (Townsend, 1928) comb. nov., S. ceylanica (Townsend, 1919) comb. nov., S. cinerea (Brauer & Bergenstamm, 1891) comb. nov., S. dammermani (Baranov, 1934) comb. nov., S. froggattii (Townsend, 1916) comb. nov., S. indica (Baranov, 1934) comb. nov., S. muscoides (Walker, 1856) comb. nov., S. rufiventris (Malloch, 1935) comb. nov., S. singgalangia (Townsend, 1927) comb. nov., and S. sumatrana (Townsend, 1927) comb. nov. The following new synonyms are proposed: Carcelia secunda Baranov, 1931 with Carcelia prima Baranov, 1931 syn. nov., Parexorista gentilis Wulp, 1893 and Carcelia (Senometopia) dentata Chao et Liang, 2002 with Parexorista ridibunda Walker, 1860 syn. nov. and Eucarcelia orientalis Shima, 1968 with Carcelia rufa Baranov, 1931 syn. nov. All known species are redescribed and illustrated, and species groupings of the genus is briefly discussed. New hosts are recorded for S. cariniforceps (Chao et Liang), S. distincta (Baranov), S. prima (Baranov), S. retrosa sp. nov. and S. yagoi sp. nov. http://www.zoobank.org/ urn:lsid:zoobank.org:pub:4845E27C-27D6-4E2A-9FBD-3F2238F1E479